Performance of The Citrus Seed Supply Chain in West Kalimantan - Didik; Meiratania, Marisa; Rusitianti, Ida (JURNAL AGRIBISAINS, 2026)
The citrus seed supply chain in West Kalimantan is currently constrained by low product quality consistency, limited supply, and untimely deliveries, as well as ineffective and inefficient supply chain performance. Therefore, a performance measurement system is essential as an approach to optimizing the network.This study to analyze the performance of the citrus seed supply chain in West Kalimantan. The method used in this study is the survey method. The research location was deliberately chosen in Sambas Regency, West Kalimantan, because this area is the center of citrus seed production in West Kalimantan. This study uses DEA data analysis. The efficiency values in each process show that the orange seed supply chain managed by the Sinar Orange farmer group has efficient performance. The efficiency value of the orange seed supply chain managed by the Sinar Orange farmer group that needs to be improved in accordance with the supply chain objective of increasing operational efficiency by reducing production costs is found in the Make process. The targets for improving the performance of the citrus seed supply chain managed by the Sinar Orange farmer group are: (1) Improving operational efficiency, (2) Improving access to information, capital, and technology, (3) Increasing the involvement of several institutions that can support the sustainability of the supply chain managed by the Sinar Orange farmer group, and (4) Building trust among supply chain members and improving horizontal coordination. These objectives can be achieved by: (1) Increasing productivity through improvements in cultivation technology, (2) Improving the types of assistance supported by coordination mechanisms among stakeholders, (3) Improving post-harvest handling, namely sorting, packaging, and storage.